A comparison of low intensity UV-C and high intensity pulsed polychromatic sources as elicitors of hormesis in tomato fruit - Scott, G.; Rupar, M.; Fletcher, A.G.D.; Dickinson, Matthew; Shama, G. (Elsevier, 2016)
Post-harvest hormetic treatment of mature green tomato fruit (Solanum lycopersicum cv. Mecano) with high intensity pulsed polychromatic light (HIPPL) significantly delayed ripening to levels comparable to those achieved using a conventional low intensity UV-C (LIUV) source. A 16 pulse HIPPL treatment reduced the ΔTCI (tomato colour index) by 50.1 % whilst treatment with a LIUV source led to a reduction of 43.1 %. Moreover, the 16 pulse treatment also induced disease resistance in the fruit to Botrytis cinerea with a 41.7 % reduction in disease progression compared to a 38.1 % reduction for the LIUV source. A single 16 pulse HIPPL treatment was found to significantly reduce disease progression on both mature green and ripe fruit with a 28.5 % reduction on ripe fruit in comparison to 13.4 % for the LIUV treatment. It is shown here that delayed ripening and disease resistance are local responses in side treated tomato fruit for both LIUV and HIPPL treatments. Finally, utilising a 16 pulse HIPPL treatment would reduce treatment times from 370 s for LIUV sources to 10 s per fruit - a 97.3 % reduction.